Cyberbullying Dilingkungan Sekolah : Upaya Pencegahan Dan Penanganannya - Rahmadani, Alvina; Khodijah, Khodijah (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 24 No 1 (2024), 2024)
Modern times bring rapid development of information technology in various parts of the world. In addition, technology also brings various positive and negative impacts in our lives. One of the negative impacts of the advancement of information technology is the emergence of cyberbullying. The rapid development of technology among adolescents increases the risk of cyberbullying behavior and this is a new problem that is a serious challenge in social life and must get full attention in the digital world. In addition, cyberbullying that occurs in the school environment has become an issue that is widely discussed in various situations. Cyberbullying has a negative impact on the mental health and academic condition of the victim. Therefore, further analysis of the factors of cyberbullying behavior is needed to find effective ways to prevent and deal with the phenomenon of cyberbullying in the school environment. This effort is carried out in the hope that students will no longer abuse social media as access to carry out cyberbullying and be wiser in using social media